2008
DOI: 10.1103/physreve.77.061107
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of an infectious disease: A large fluctuation in a nonequilibrium system

Abstract: We develop a theory of first passage processes in stochastic non-equilibrium systems of birthdeath type using two closely related epidemiological models as examples. Our method employs the probability generating function technique in conjunction with the eikonal approximation. In this way the problem is reduced to finding the optimal path to extinction: a heteroclinic trajectory of an effective multi-dimensional classical Hamiltonian system. We compute this trajectory and mean extinction time of the disease nu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
169
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(172 citation statements)
references
References 18 publications
2
169
1
Order By: Relevance
“…Such a path integral representation has been derived for the case of a Michaelis-Menten enzyme attached to the membrane of a eukaryotic cell and later generalized to a network of reactions [23]. This theory is valid in the limit of short-lived mRNA [16][17][18][19][20][21][22][23][24][25][26][27][28]. Our first step is to consider the process of mRNA generation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a path integral representation has been derived for the case of a Michaelis-Menten enzyme attached to the membrane of a eukaryotic cell and later generalized to a network of reactions [23]. This theory is valid in the limit of short-lived mRNA [16][17][18][19][20][21][22][23][24][25][26][27][28]. Our first step is to consider the process of mRNA generation.…”
Section: Methodsmentioning
confidence: 99%
“…This semi-classical method has been used earlier to calculate rare event statistics in reaction diffusion systems [25] and it has been applied to various epidemiological stochastic models [24,26,27]. In this method, we start with the eikonal ansatz:…”
Section: Methodsmentioning
confidence: 99%
“…Specifically we employ the Wentzel-Kramers-Brillouin (WKB) method to derive quantitative predictions for fixation times. Examples of using the WKB method to describe the escape from metastable states include the computation of mixing times in evolutionary games (Black et al 2012), investigating extinction processes in coexisting bacteria (Lohmar and Meerson 2011) or predator-prey systems (Gottesman and Meerson 2012), and investigating epidemic models (van Herwaarden and Grasman 1995;Kamenev and Meerson 2008;Dykman et al 2008;Black and McKane 2011;Billings et al 2013). In the presence of recombination, Altland et al (2011) have shown that metastable states can appear when recombination rates are large, even if the double mutant is advantageous.…”
mentioning
confidence: 99%
“…Instead, minimum-action Hamiltonian trajectories must be computed. Problems of this type are usually tackled in one of two ways: first, the equations of motion could be integrated using a shooting method to find the optimal (most likely) trajectory with a given final point (Kamenev and Meerson 2008;Black and Mckane 2011;Gottesman and Meerson 2012); second, the equations can be integrated using an iterative scheme, which converges to the optimal trajectory (Lohmar and Meerson 2011) connecting given start and end points. We found that the second method quickly converges for our problem, so results presented in the following use this method.…”
mentioning
confidence: 99%
“…Besides its fundamental interest for non-equilibrium physics, the function φ is important in various applications, e.g. for calculating escape rates from metastable states, with applications ranging from chemistry and population dynamics to cosmology [1][2][3][4][5][6]9].In a non-equilibrium steady-state, to compute the probability of a rare-event, one must calculate the dynamics leading up to that event [10]. This is in general a difficult task, even more so for spatially extended systems, where only a handful of analytical solutions exist [11].…”
mentioning
confidence: 99%